Screening of rice genotypes for resistance to bakanae disease - A. SINGH, S. SUNDER, SATYAVIR and (Indian Phytopathology, 2002)
A collection of 221 scented and non-scented rice genotypes were screened for resistance to bakanae disease, caused by Gibberella fujikuroi, during kharif 1993 and 1994 at the CCS Haryana Agricultural University Regional Research Station, Uchani, Karnal, Haryana, India. Observations on disease incidence were recorded 15 and 30 days after transplanting and genotypes were classified in different categories following the standard evaluation system for rice. Among 124 scented genotypes evaluated, 2 genotypes (C 4-64 and KarjatX13-21) were resistant, 8 were moderately resistant and the rest were susceptible to the disease. Out of 97 non-scented genotypes evaluated, 4 genotypes (BR 1067-84-1-3-2-1, BR 1257-31-1-1, BR 4363-8-11-4-9 and IR 58109-109-1-1-3) were highly resistant while genotypes AS 34011, BG 936, CNA 3886, HKR 86-104, IR 39464-54-1-3-2-1-3 and PR 106 were resistant. Of the remaining genotypes, 52 were graded as moderately resistant and 35 as moderately susceptible.